High Temperature Corrosion - Ahmad, Zaki; Ahmad, Zaki (IntechOpen, 2016)
High temperature corrosion is an extremely important area of corrosion as it causes the failure of high temperature equipment in process industry and power generation. Every engineer is required to obtain a basic knowledge of high temperature corrosion to prevent the colossal damage caused by it. This book contains chapters ranging from basic to advance topics to create an understanding of high temperature of various metals and alloys. With the emerging technologies such as nanotechnology, their role in controlling high temperature corrosion needs to be comprehended and new techniques developed to control high temperature corrosion. It is hoped that this book would fulfill these objectives and aspirations of the readers. Note from the publisher: It is with great sadness and regret that we inform the contributing authors and future readers of this book that the Editor, Prof. Zaki Ahmad passed away shortly after finishing the book and before having a chance to see its publication. Prof. Ahmad was InTech's long term collaborator and edited his first book with us in 2011 (''Recent Trends in Processing and Degradation of Aluminium Alloys''). The book ''High Temperature Corrosion'' was his fourth edited volume. The fruitful collaboration continued until his final days when he was acting as a co-editor on a book ''Wastewater Treatment and Resource Recovery''. We would like to acknowledge Dr. Zaki Ahmad's contribution to open access scientific publishing, which he made during 6 years of dedicated work on edited volumes and express our gratitude for his pleasant cooperation with us.
English
Keywords: Biotechnology; Surface-coating technology